Optimization of Fe2+ Removal from Coal Mine Wastewater using Activated Biochar of Colocasia esculenta. (1st September 2017) - Banerjee, Soumya; LaminKa‐ot, Augustine; Joshi, S. R.; Mandal, Tamal; Halder, Gopinath
ABSTRACT: : The present study investigates the sorptive removal of Fe 2+ from simulated coal mine waste water using steam activated biochar (SABC) developed from the roots of Colocasia esculenta . The process was optimized by response surface methodology (RSM) under the influence of pH, temperature, adsorbent dosage and contact time at a constant shaking speed of 180 rpm with an initial concentration of 3 mg/L. The uptake performance of the biosorbent was assessed following a 2 4 full factorial experimental matrix developed by central composite design approach. Adsorbent was characterised by SEM, EDAX, XRD and B.E.T surface area analyzer. Maximum removal of 72.96% of Fe 2+ was observed at pH 7.75, temperature 37.5 °C, adsorbent dosage 1.5 g/L for a time period of 180 mins. The study suggested that SABC prepared from roots of Colocasia esculenta could be used as an efficient and cost effective sorbent for removal of Fe 2+ from coal mine wastewater.